2018
DOI: 10.1177/2324709618780422
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Raoultella planticola Urinary Tract Infection in a Patient With Immunoglobulin A Nephropathy

Abstract: Raoultella planticola is a gram-negative, aerobic, nonmotile mostly found in environments with high prevalence in soil and water. This organism is a very rare human pathogen as only 29 cases of Raoultella planticola–related infections have been reported until 2017, with only 7 cases in the United States. Only 3 cases of urinary tract infection secondary to R planticola have been reported, 1 in a pediatric patient and 2 in adults. In this article, we present a case of R planticola urinary tract infection in a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…Urine culture showed the presence of R. planticola bacteria, which were sensitive to all major antibiotics, including ceftriaxone, ciprofloxacin, nitrofurantoin, cefazolin, gentamicin and trimetoprim-sulfamethoxazole. As a result of antibiotic therapy, the patient was cured without complications [16].…”
Section: Discussionmentioning
confidence: 92%
“…Urine culture showed the presence of R. planticola bacteria, which were sensitive to all major antibiotics, including ceftriaxone, ciprofloxacin, nitrofurantoin, cefazolin, gentamicin and trimetoprim-sulfamethoxazole. As a result of antibiotic therapy, the patient was cured without complications [16].…”
Section: Discussionmentioning
confidence: 92%
“…Other cases include reports of pneumonia, wound infection, cholangitis, bacteremia and conjunctivitis (Serkan et al, 2018). In this case, we present a patient with a confirmed case of Raoultella planticola urinary tract infection (Mehmood et al, 2018;Serkan et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…It is a histamine-producing bacterium generally found in aquatic environments, in fish and in soil (Lam and Salit, 2017). It is not generally thought to be pathogenic, but recent cases of human infection are emerging, most commonly in fragile, frequently hospitalized patients with multiple comorbidities and in the pediatric population (Kalaria et al, 2017;Mehmood et al, 2018;Serkan et al, 2018;Skelton et al, 2017;Xu et al, 2016). There is one concerning case report of carbapenem resistance with R. planticola infection (Skelton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One retrospective study found that 56% of the patients with a UTI due to R planticola were immunodeficient; 28% of these being solid organ transplant recipients . Additionally, most case reports describe R planticola as pan‐sensitive to most antimicrobial options including penicillins and cephalosporins, with the reports of resistance describing non‐susceptibility to ampicillin and piperacillin . These case reports of UTI due to R planticola describe successful treatment with agents such as ceftriaxone, ciprofloxacin, cephalexin, and ampicillin/sulbactam.…”
Section: Discussionmentioning
confidence: 99%